Specific Skill Requirements Within Prefabricated Residential Construction: Stakeholders’ Perspectives - Rotimi, FE; Almughrabi, FM; Samarasinghe, DAS; Silva, C (MDPI, 2022)
Skill availability is an important component in the uptake of prefabrication and plays a crucial role in housing supply. However, the challenge is that the demand for housing has outgrown the availability of specifically trained workers. This challenge is not unique to New Zealand; many developed countries worldwide are facing similar issues. Therefore, the purpose of this study is to determine relevant skills in the prefabricated residential construction sector in New Zealand (NZ) and suggest improvement measures from the standpoint of industry stakeholders. The study adopted a semi-structured online survey and administered it to multiple construction industry practitioners. The study found the training of the construction workforce as one significant area of focus. In addition, external sourcing of international prefabrication-specific skilled workers could improve the issues of skill shortages in the residential prefabrication sector. Furthermore, the study revealed that the barriers to healthier prefabrication uptake are closely linked to shortages in management, digital architecture and design, and vocational skills related to residential construction. The study has contributed to the current pool of knowledge by identifying skill issues in NZ’s prefabricated residential construction sector, classifying the major restraints limiting prefabrication implementation, and determining measures for increasing industry uptake. It is anticipated that this will help construction organizations and the wider industry develop strategic goals and a roadmap for meeting the skill requirements in NZ. Training policies and programmes can be developed with focus on crucial prefabrication skill requirements at governmental level. Curriculum reviews are recommended for uptake by academic and vocational institutions.
Keywords: Prefabrication; Skills; Training; Vocational